Pengaruh Modal Usaha Dan Penetapan Harga Terhadap Pendapatan Usaha Kuliner Pada Usaha Mikro Di Kecamatan Tidore Selatan - Jakin, Rahayu S.Hi.; Dahlan, Fadli; Ruray, Titiek Arafiani (Jurnal Ilmiah Wahana Pendidikan, 2025)
This study aims to determine the effect of business capital and pricing on culinary business revenue in micro-enterprises in South Tidore District. This study uses a quantitative method with a population of 77 active culinary businesses in South Tidore District. The results of the study indicate that the business capital variable has a positive and significant effect on revenue, as indicated by a coefficient value of 0.423, with a calculated t-value of 4.069 > t-table 1.992 and a significance level of 0.000 < 0.05. The pricing variable also has a positive and significant effect on revenue, with a coefficient value of 0.498, a calculated t-value of 5.283 > t-table 1.992, and a significance level of 0.000 < 0.05. Simultaneously, business capital and pricing have a significant effect on culinary business revenue, as evidenced by a calculated F-value of 228.719 > F-table 3.119 and a significance level of 0.000 < 0.05. Thus, it can be concluded that the greater the business capital and the more appropriate the pricing applied, the higher the income obtained by micro culinary businesses in South Tidore District.